Multiplexed-shotgun-genotyping data resolve phylogeny within a very recently derived insular lineage - Mort, Mark E. (2022)
Premise of the study: Endemic plants on oceanic islands have long served as model systems for studying patterns and processes of evolution. However, phylogenetic studies of island plants frequently illustrate a decoupling of molecular divergence and ecological/morphological diversity, resulting in phylogenies lacking the resolution required to interpret patterns of evolution in a phylogenetic context. The current study uses the primarily Macaronesian fl owering plant genus Tolpis to illustrate the utility of multiplexed shotgun genotyping (MSG) for resolving relationships at relatively deep (among archipelagos) and very shallow (within archipelagos) nodes in this small, yet diverse insular plant lineage that had not been resolved with other molecular markers. • Methods: Genomic libraries for 27 accessions of Macaronesian Tolpis were generated for genotyping individuals using MSG, a form of reduced-representation sequencing, similar to restriction-site-associated DNA markers (RADseq). The resulting data fi les were processed using the program pyRAD, which clusters MSG loci within and between samples. Phylogenetic analyses of the aligned data matrix were conducted using RAxML. • Key results: Analysis of MSG data recovered a highly resolved phylogeny with generally strong support, including the fi rst robust inference of relationships within the highly diverse Canary Island clade of Tolpis . • Conclusions: The current study illustrates the utility of MSG data for resolving relationships in lineages that have undergone recent, rapid diversifi cation resulting in extensive ecological and morphological diversity. We suggest that a similar approach may prove generally useful for other rapid plant radiations where resolving phylogeny has been diffi cult.